PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN SIKAP MORAL SISWA KELAS VIII SMP TRI BHAKTI PEKANBARU T.P 2015/2016 - Nur Azizah; Elni Yakub; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Adolescence is the most critical period in social situations, it is often experienced by junior high school students who are the transition periods to a teenager. This transition period of teenage students has undergone a change in the role of social morality with peers so that teenagers want to show and show identity, but that seems to be the attitude of students who deviate from the norms of courtesy and existing etiquette. This research aims to find the effect of group guidance services on the improvement of students' moral attitudes. The research method used in this study is the quasi exsperimen using the one group pre-test pos test design. This study is conducted twice before the experiment (pre test) After the experiment with one subject group. Data analysis used in this research is descriptive analytic. The subject in this research is chosen by using non probability sampling technique with purposive sampling method of 30 students, the method of collecting this data is questionnaire. The result of research This shows that there is influence of group guidance on improvement of moral attitude of student 27%, while 73% influenced by variable or other factor such as environment, family, school.Keywords : Group Guidance Services,Attitude,Moral